Genome editing for primary immunodeficiencies: A therapeutic perspective on Wiskott-Aldrich syndrome - Naseem, Asma; Steinberg, Zohar; Cavazza, Alessia (Frontiers in Immunology, 2022)
Primary immunodeficiency diseases (PIDs) are a group of rare inherited disorders affecting the immune system that can be conventionally treated with allogeneic hematopoietic stem cell transplantation and with experimental autologous gene therapy. With both approaches still facing important challenges, gene editing has recently emerged as a potential valuable alternative for the treatment of genetic disorders and within a relatively short period from its initial development, has already entered some landmark clinical trials aimed at tackling several life-threatening diseases. In this review, we discuss the progress made towards the development of gene editing-based therapeutic strategies for PIDs with a special focus on Wiskott-Aldrich Syndrome, and outline their main challenges as well as future directions with respect to already established treatments.